Using a new fish indicator-based index with scoring and evaluation criteria to assess the ecological status in a disturbed subtropical river of China - Wang, Sai; Gao, Yu-Jia; Wu, Dong-Hai; Xu, De-Lin; Wang, Tuan-Tuan; Fan, Shi-Di; Wu, En-Ni; Song, Yong-Duo; Zhang, Hong-Jin; Fu, Guo-Ping; Chen, Zhong-Bing; Mo, Ling; et al. (Frontiers in Ecology and Evolution, 2024)
Rivers are constantly disturbed by anthropogenic stressors. Developing robust biotic indicators to assess river environments across large spatial scales is important.In the subtropical Liuxi River of China, 34 native fish indicators, including 4 genera and 30 species, were selected from 108 fish species by linear discriminant analysis.These indicators were grouped into 19 ecological items and assigned evaluation scores according to the roles they played in the food web (e.g., keystoneness and trophic level) and their positive feedback on the environment (e.g., requirements for feeding, spawning/nursing, and migrating). Three formulae for calculating the index of fish indicators (IFI) were developed based on the scoring of each indicator and weighted by relative abundance (individual number, i.e., IFIN) and relative biomass (wet weight, i.e., IFIB). Spearman correlation analysis showed that IFIB, which had positive (P < 0.05) correlations with elevation (m), dissolved oxygen (mg/L), flow velocity (cm/s), Shannon-Wiener diversity, benthic index of biotic integrity, exhibited a more powerful explanation of biodiversity and environmental factors than IFIN and unweighted IFI. Therefore, IFIB was most suitable for constructing a scoring system to evaluate ecological status (e.g., water and habitat quality). These results suggested that fish indicator-based scoring and evaluation system was effectively in not only assessing the site-or region-specific ecological status bot also reflecting the fluvial biodiversity and food web integrity. Further application and promotion of this indicator-based evaluation method may improve field investigation efficiency and contribute greatly to the conservation and management of river ecosystems.